Counteracting age-related loss of skeletal muscle mass: a clinical and ethnological trial on the role of protein supplementation and training load (CALM Intervention Study): Study protocol for a randomized controlled trial- no UMP affiliation - Bechshøft, Rasmus Leidesdorff; Reitelseder, Søren; Højfeldt, Grith; Castro-Mejía, Josué Leonardo; Khakimov, Bekzod; Hajar Fauzan, Ahmad; Kjær, Michael; Engelsen, Søren Balling; Johansen, Susanne Margrete Bølling; Rasmussen, Morten Arendt; Lassen, Aske Juul; Jensen, Tenna; et al. (2016)
Aging is associated with decreased muscle mass and functional capacity, which in turn decrease quality of life. The number of citizens over the age of 65 years in the Western world will increase by 50 % over the next four decades, and this demographic shift brings forth new challenges at both societal and individual levels. Only a few longitudinal studies have been reported, but whey protein supplementation seems to improve muscle mass and function, and its combination with heavy strength training appears even more effective. However, heavy resistance training may reduce adherence to training, thereby attenuating the overall benefits of training. We hypothesize that light load resistance training is more efficient when both adherence and physical improvement are considered longitudinally. We launched the interdisciplinary project on Counteracting Age-related Loss of Skeletal Muscle Mass (CALM) to investigate the impact of lifestyle changes on physical and functional outcomes as well as everyday practices and habits in a qualitative context.